Internet: a new challenge for teachers - Abreu, Rosane de Albuquerque dos Santos; Nicolaci-da-Costa, Ana Maria (Paidéia (Ribeirão Preto), 2003)
Penetration of the new digital technologies in schools has become a challenge for educators. The use of computers has already been absorbed by them but they seem to find the Internet more difficult to deal with. Review of the specialized literature points out that the use of the latter is seen by them as more threatening and complex and that this view is at least partially caused by emotional factors. Given that these studies do not investigate such emotional factors in depth, an exploratory investigation was conducted in order to do so. Ten teachers, who were engaged in different school activities and had been using the Internet for at least two years, were interviewed. Analysis of their discourse during the interviews yielded interesting results. Even though they use the Internet instrumentally for work (mainly research) purposes, its use for educational objectives seems be a source of internal conflicts, and represents a potential of radical changes in traditional pedagogy and as such, a menace to their traditional role as teachers. They do not know how to be educators in a networked society and this makes them very anxious.